PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP MINAT DAN HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Suniyah; Asrizal Wahdan Wilsa; Dadang Suhada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyzer the effect of the Teams Games Tournament (TGT) cooperatife learning model on students interest and learning outcomes in mathematics. This research employed an experimental method using a pretest - posttest control group design. The sample consisted of 50 fifth- grade students divided into experimental and control classes. Data were collected using learning interest questionnaire and achievement tests. Data analysis used an independent sample t test. The results showed a significant effect of TGT on learning interest (sig. 0. 003 < 0. 005) and learning outcomes (sig. 0. 044 < 0. 05). Therefore TGT is effective in improving student interest and learning outcomes.